Math
posted by Bob on .
How to rewrite an expression with negative exponents such as :
12(3x1)^5 *(6x+7)^5 + 30(3x1)^4 *(6x+7)^4
common factor is 6 but what can I pull out from the (3x1)^5 and (3x1)^4 ?

( 3 x  1 ) ^ 5 = 1 / ( 3 x 1 ) ^ 5
( 3x  1 ) ^  4 = 1 / ( 3 x 1 ) ^ 4
 12 ( 3 x 1 ) ^  5 * ( 6 x + 7 ) ^ 5 + 30 ( 3 x  1 ) ^  4 * ( 6 x + 7) ^ 4 =
[  12 ( 6 x + 7 ) ^ 5 ) + 30 * ( 3 x  1 ) * ( 6 x + 7 ) ^ 4 ] / ( 3 x  1 ) ^ 5 =
6 * ( 6 x + 7 ) ^ 4 * [ (  2 ) * ( 6 x + 7 ) + 5 * ( 3 x  1 ) ] / ( 3 x  1 ) ^ 5 =
6 * ( 6 x + 7 ) ^ 4 * (  12 x  14 + 15 x  5 ) / ( 3 x  1 ) ^ 5 =
6 * ( 6 x + 7 ) ^ 4 * ( 3 x  19 ) / ( 3 x  1 ) ^ 5